2011
DOI: 10.1177/1087057111415525
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel P2Y14 Agonist and Antagonist Using Conventional and Nonconventional Methods

Abstract: IntroductIon Purine and pyrimidine nucleotides are potent extracellular signaling molecules, are released by most tissues, and exert their effects by interacting with two classes of membrane receptors, p2X and p2y. p2y receptors are members of the large metabotropic G-protein-coupled receptor (Gpcr) family and are involved in numerous biochemical processes, including platelet function and chloride ion flux. p2y1, p2y11, p2y12, and p2y13 are activated by adenine nucleotides such as adp and atp; in contrast, p2y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Hamel et al (2011) also screened a phosphonate library using a [ 3 H]UDP binding assay to identify several molecules that were concluded to bind to the P2Y 14 -R in the low micromolar range.…”
Section: Discussionmentioning
confidence: 99%
“…Hamel et al (2011) also screened a phosphonate library using a [ 3 H]UDP binding assay to identify several molecules that were concluded to bind to the P2Y 14 -R in the low micromolar range.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other studies Carter et al demonstrated that uridine diphosphate acted also as agonist of human P2Y14R [22]. Intracellular calcium mobilization and nonconventional cellular impedance functional assays showed that UMP, UDP, and UTP uncoupled to glucose also activated P2Y14-expressing cells [23]. …”
Section: Resultsmentioning
confidence: 97%
“…Chambers et al reported that ADP-glucose, UMP, UDP, and UTP as well as uridine were unable to activate P2Y14 [21, 23]. The discovery by Carter et al that UDP also acts as a potent agonist revealed that a sugar moiety is not required for activation of the P2Y14 receptor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where antagonists used for animal studies, the substance is underlined and where clinical trials are ongoing is typed in bold. P2Y14 compound 18q, compound A, pro-drug 7j [10,12,52,60] prostaglandin [69] and EDHF [71,72] from ECs, might be responsible for the vasorelaxing effect. Since P2Y 2 activation causes the same vasorelaxation in eNOS -/-mice as it does in wild type mice, a major role of EDHF as mediator is implied [43].…”
Section: Purinoceptor Agonistsmentioning
confidence: 98%